Impact of interlayer on moisture characteristics of reclaimed soil backfilled with Yellow River sediments - Wang, Xiaotong; Hu, Zhenqi; Liang, Yusheng (International Journal of Agricultural and Biological Engineering, 2020)
Underground coal mining causes land subsidence, and backfilling with Yellow River sediment is an effective reclamation technology to restore farmland in China. To date, two-layer soil reconstructed (TSR) for subsided land reclamation resulted in poor capacity to retain water. To solve this problem, multi-layered soil reconstructed (MSR), sandwiching soil interlayers between sediment, was developed as a new reclamation strategy with Yellow River sediment. In order to evaluate the impact of soil interlayer on moisture characteristics, laboratory experiments of infiltration and evaporation were conducted. Two control treatments (CK1, CK2) and four experimental treatments (T1-T4) were designed. CK1 was undamaged farmland, CK2 was conventional reconstructed two-layers soil profile (filled sediment with 40 cm soil cover). T1-T4 were multiple-layers soil profiles sandwiching different structures of soil interlayers between sediment layers. The results indicated that putting interlayers into sediment reduced water leakage and water evaporation, improved the water-holding capacity of conventional two-layer soil profiles. The total thickness of soil interlayers of 30 cm (T3 and T4) was better than 20 cm (T1 and T2) and two soil interlayers (T2) were better than one (T1) on water-holding capacity. Furthermore, the best reconstructed soil profile was T3, sandwiched two soil interlayer and the first thickness was 20 cm. This treatment had the greatest improvement on soil water holding capacity with an increase of 49.14% compared to CK2 at the end of the evaporation and was closest to CK1 (402.31 mm). This study provided experimental evidence that compares with TSR, MRS improved the moisture characteristics of backfilling with Yellow River sediment.Keywords: land reclamation, Mining subsidence, Yellow River sediment, multi-layered soil reconstructed, moisture characteristicsDOI: 10.25165/j.ijabe.20201301.5418Citation: Wang X T, Hu Z Q, Liang Y S. Impact of interlayer on moisture characteristics of reclaimed soil backfilled with Yellow River sediments. Int J Agric & Biol Eng, 2020; 13(1): 153–159.